Canadian federalism and treaty powers : organic constitutionalism at work - Cyr, Hugo (Collection "Diversitas" ;, 2009)
With the increased mobility and interdependence brought on by globalisation, governments can no longer deal effectively with what were traditionally regarded as «domestic issues» unless they cooperate among themselves. International law may once have been a sort of inter-state law concerned mostly with relations between states, but it now looks increasingly inside state borders and has become, to a large degree, a trans-governmental law. While this creates significant challenges even for highly-unified «nation-states», the challenges are even greater for federations in which powers have been divided up between the central government and federated states. What roles should central governments and federated states play in creating and implementing this new form of governance?